Assessing health-related quality of life in Japanese children with a chronic condition: validation of the DISABKIDS chronic generic module - Hatoko Sasaki (Health and Quality of Life Outcomes, 2018)
Abstract Background This study examined the reliability and validity of the Japanese versions of the DISABKIDS-37 generic modules, a tool for assessing the health–related quality of life (HRQOL) of children and adolescents with a chronic condition. Methods The study was conducted using a sample of 123 children/adolescents with a chronic medical condition, aged 8–18 years, and their parents. Focus interviews were performed to ensure content validity after translation. The classical psychometric tests were used to assess reliability and scale intercorrelations. The factor structure was examined with confirmatory factor analysis (CFA). Convergent validity was assessed by the correlation between the total score and the sub-scales of DISABKIDS-37 as well as the total score of KIDSCREEN-10. Results Both the children/adolescent and parent versions of the score showed good to high internal consistency, and the test-retest reliability correlations were r = 0.91 or above. The CFA revealed that the modified models for all domains were better fit than the original 37 item scale model for both self-report and proxy-report. Moderate to high positive correlations were found for the associations within DISABKIDS-37 sub-scales and between the subscales and total score, except for the treatment sub-scale, which correlated weakly with the remaining sub-scales. The total score of the child-reported version of KIDSCREEN-10 correlated significantly and positively with the total score and all the sub-scales of the child-reported version of DISABKIDS-37 except the Treatment sub-scale in adolescents. Conclusions The modified models of Japanese version of DISABKIDS generic module were psychometrically robust enough to assess the HRQOL of children with a chronic condition.